Cover Image, Volume 119, Number 4, April 2022. Issue 4 (10th March 2022) - Belliveau, Jessica; Papoutsakis, Eleftherios T.
Abstract : The cover image is based on the Article Extracellular vesicles facilitate large-scale dynamic exchange of proteins and RNA among cultured Chinese hamster ovary and human cells by Jessica Belliveau and Eleftherios T. Papoutsakis., https://doi.org/10.1002/bit.28053 .